Barriers stopping LGBTI people from accessing LGBTI police liaison officers: analysing interviews with community and police. Issue 3 (2nd July 2020) - Dwyer, Angela; Ball, Matthew; Lee, Murray; Crofts, Thomas; Bond, Christine
ABSTRACT: Police liaison programs that support LGBTI (lesbian, gay, bisexual, transgender, intersex) people might go by many names (including GLLOs, LGBTI police liaison officers, etc.), but they have become the key model for providing police service enhancements for LGBTI people. These programs now dominate approaches used by police to build relationships between police and LGBTI communities, yet research on the effectiveness of these programs is limited. This paper examines interview data from LGBTI people and LGBTI police liaison officers in three states in Australia. The interviews were part of a broader study of LGBTI police liaison programs, which included a survey of LGBTI people about the issues they think impact upon these programs. The analysis demonstrates the key issues that stop LGBTI people from seeking support from LGBTI police liaison officers and how we might potentially improve this situation.